AN ANALYSIS OF ENGLISH TEACHER’S LESSON PLAN REFERRING TO MERDEKA BELAJAR PROGRAM AT SMK PGRI 2 OF PALEMBANG - Utami Cahyani; Ferri Hidayad; Evi Rosmiyati (Universitas PGRI Palembang, 2024)
The aims of this study was to know the ways or the stages use by the English teachers to design Merdeka Belajar lesson plan and to find out the difficulties face by the English teachers in designing the Merdeka Belajar lesson plan. The method of this study was qualitative descriptive method. The techniques of collecting data was using triangulation, which are observation, interview and also documentation. The interview conducted with three English teachers at SMK PGRI 2 of Palembang. After the data was obtained, the next step that the process of reducing the data occurring repeatedly. The results showed that for the first year, teachers were still confused about implementing Merdeka Belajar curriculum. So, teachers at SMK PGRI 2 Palembang have already join In House Training (IHT), in 2021 and 2022. Although the teacher faced some difficulties and obstacles such as lack of experience, inadequate infrastructure facilities from school, and there are some still confused about the learning system. To overcome that difficulties, teacher’s at SMK PGRI 2 of Palembang learn from the Merdeka Mengajar platfrom and collaborate with each teacher.